Влияние условий гипо- и гипертермии на функционирование хлорных каналов плазмалеммы клеток Nitella flexilis - Найдун, Светлана Николаевна; Юрин, Владимир Михайлович (Минск : БГУ, 2002)
With using of microelectrode techniques was investigates the reorganisation, developing at change, in work of the basic ion-transport systems of plant cell plasma membranes after long-term influence of high temperature environments. As modelling object the crates Nitella flexilis were used. The measurements were carried out in conditions of room temperature (18-20 °C) after 1-25-days of exposition of cells at 32 0C and +4 °C. It has been shown, that conductances of excitable chloride channels are lowered, since 2-4 day of increased decreased temperature influence. The maximal currents of chloride channels decreased by 8 to 10 fold. The temperature influences did not cause changes of processes of activation and deactivation of chloride channels of plasmalemma Nitella flexills.